56 Streamlining Referral Processes at a Tertiary Acute Medical Ambulatory Centre. (16th September 2019) - O'Donovan, Claire; Wright, Steve; Towler, Simon; Furness, Erin
Abstract: Background: The Acute Medical Ambulatory Centre (AMAC) was established with the goals of facilitating early discharge and preventing avoidable medical admissions. 12 months post its introduction, the service was inefficient and operating under capacity. A project aimed to improve the AMAC referral processes and increase the centre's overall efficiency was undertaken. Methods: Western Australia Department of Health Clinical Service Redesign methodology (a blend of Lean and Six Sigma methodologies) was used to complete the project. This involved process mapping, root cause analysis and solutions sessions with stakeholders, as well as a semi-structured phone interview with patients. Results: Transition from a paper-based to an electronic referral system. Creation of an 'AMAC Quick Reference Guide' for doctors. Production of an AMAC contact card to be given to patients on discharge if they   have AMAC follow up. Letters detailing the patient review are forwarded on the day of the appointment facilitating timely feedback to GPs. An AMAC information flyer for GPs is now available on the hospital website. Conclusion: Redesigning the referral process to the AMAC has improved workflow and efficiency with significant improvements in staff satisfaction. The institution is aiming to become paperless and this redesign project has led to the elimination of another paper form. The success of the project is testament to the engagement of the staff involved and demonstrates the need for doctors to not only engage their medical colleagues, but also nursing and clerical staff. The redesign project has helped refocus hospital priorities and should hopefully see further support for the centre; developing the ambulatory model of care as an integral part of the service provided. Other centres can learn valuable lessons from our experience and develop similar strategies to cope with the ever-increasing demands on the public healthcare system.